"I thought it was all about wining and dining, parties and celebrities" - an insight into final year public relations students' perception of the communications industry - Wolf, Katharina (School of Marketing, Curtin Business School, 2009)
Are students prepared for the day to day challenges of the communications industry by the time they are completing their final year? This research addresses students pre- and frequently misconceptions as they embark on their studies, contrasted to their understanding of the discipline after having completed all core units of the public relations stream. By focusing on students enrolled in a final year, compulsory placement unit, this study investigates the role industry placements play in providing students with a realistic understanding of their chosen discipline before entering the employment market. This in turn re-opens the debate about the importance of work integrated learning opportunities and particularly placement units as an integral element of a communications degree.